Alginate oligosaccharide improves resistance to postharvest decay and quality in kiwifruit (Actinidia deliciosa cv. Bruno) - Ruiling Zhuo; Boqiang Li; Shiping Tian (Horticultural Plant Journal, 2022)
Kiwifruit is an extremely perishable fruit; postharvest disease and senescence during storage can reduce the fruit quality, resulting in economic loss. Considerable research effort has focused on identifying safe and cost-effective ways to preserve fresh kiwifruit. To this end, the present study investigated the effects of alginate oligosaccharide (AOS) soaking treatment on postharvest quality and disease in the ‘Bruno’ variety of kiwifruit. The involved physiological mechanisms were further explored. The results showed that AOS did not inhibit the growth of Botrytis cinerea in vitro, the causal agent of gray mold in kiwifruit, but reduced the incidence of gray mold and diameter of lesions of kiwifruit during storage. Kiwifruit treated with 50 mg · L−1 AOS showed a higher degree of firmness and lower soluble solid content than control fruit treated with distilled water. Moreover, AOS treatment inhibited the activity of polygalacturonase and pectinesterase, while enhancing the activity of polyphenoloxidase, l-phenylalanine ammonia lyase and β-1,3-glucanase related to pathogen defense, and also improved total antioxidant capacity determined by the DPPH, FRAP, and ABTS methods in kiwifruit. These results indicate that 50 mg · L−1 AOS can confer disease resistance in kiwifruit during storage.